Successful Management of Left Sided Post-Cervical Uterine Torsion in Goat with Modified Schaffer’s Method - Ramteke, S. S.; Koli, A.B.; Natkar, S. B.; Yewle, L. V.; Patil, A D (Animal Reproduction Update, 2022)
A Non-descript doe with completion of gestation period with the history of straining, restlessness and engorged udder was brought to the Teaching Veterinary Clinical Complex, College of Veterinary and Animal Sciences, Udgir. Per-vaginal examination revealed that the Goat has post-cervical left sided uterine torsion of more than 180° which was successfully treated by modified Schaffer’s method. The live female kid was delivered with gentle traction. An uneventful recovery was seen after the kidding and treatment with Antibiotic and Supportive therapy for three days.